Integral Terhadap Pemikiran Hermeneutis Nasr Hamid Abu Zayd: Atas Tafsir Kontekstual QS. An-Nisā’ [4]:3” - Rahmatunnaimah; Ade Afriansyah (EL-MAQRA', 2026)
This study aims to critically analyze Nasr Hamid Abu Zayd’s hermeneutical approach in interpreting Q.S. An-Nisa [4]:3 and to compare it with classical exegesis. This research employs a qualitative approach using library research and hermeneutic-philosophical analysis. The findings reveal that classical tafsir generally interprets the verse within a normative-legal framework as a basis for the permissibility of polygamy, limited by numerical restriction and the condition of justice. In contrast, Abu Zayd offers an ethical-contextual interpretation, viewing the verse as a form of restriction on pre-Islamic polygamous practices that leads toward justice and a tendency toward monogamy. The comparative analysis shows that the difference lies not only in the interpretive outcomes but also in their epistemological foundations, where classical tafsir is oriented toward legal stability, while Abu Zayd’s approach is dynamic and context-sensitive. The critical evaluation indicates that Abu Zayd’s hermeneutics is relevant to contemporary issues but faces challenges, particularly the risk of interpretive relativism and the reduction of the transcendental dimension of revelation. Therefore, his approach should be positioned as a critical complement to classical exegesis in developing contemporary Qur’anic studies.